Mitochondrial DNA D-loop variants correlate with a primary open-angle glaucoma subgroup - Vallbona-Garcia, Antoni; Lindsey, Patrick J.; Kamps, Rick; Stassen, Alphons P. M.; Nguyen, Nhan; van Tienen, Florence H. J.; Hamers, Ilse H. J.; Hardij, Rianne; van Gisbergen, Marike W.; Benedikter, Birke J.; de Coo, Irenaeus F. M.; Webers, Carroll A. B.; et al. (Frontiers in Ophthalmology, 2024)
Primary open-angle glaucoma (POAG) is a characteristic optic neuropathy, caused by degeneration of the optic nerve-forming neurons, the retinal ganglion cells (RGCs). High intraocular pressure (IOP) and aging have been identified as major risk factors; yet the POAG pathophysiology is not fully understood. Since RGCs have high energy requirements, mitochondrial dysfunction may put the survivability of RGCs at risk. We explored in buffy coat DNA whether mtDNA variants and their distribution throughout the mtDNA could be risk factors for POAG. The mtDNA was sequenced from age-and sex-matched study groups, being high tension glaucoma (HTG, n=71), normal tension glaucoma patients (NTG, n=33), ocular hypertensive subjects (OH, n=7), and cataract controls (without glaucoma; n=30), all without remarkable comorbidities.No association was found between the number of mtDNA variants in genes encoding proteins, tRNAs, rRNAs, and in non-coding regions in the different study groups. Next, variants that controls shared with the other groups were discarded. A significantly higher number of exclusive variants was observed in the Dloop region for the HTG group (~1.23 variants/subject), in contrast to controls (~0.35 variants/subject). In the D-loop, specifically in the 7S DNA sub-region within the Hypervariable region 1 (HV1), we found that 42% of the HTG and 27% of the NTG subjects presented variants, while this was only 14% for the controls and OH subjects. As we have previously reported a reduction in mtDNA copy number in HTG, we analysed if specific D-loop variants could explain this. While the majority of glaucoma patients with the exclusive Dloop variants m.72T>C, m.16163 A>G, m.16186C>T, m.16298T>C, and m.16390G>A presented a mtDNA copy number below controls median, no significant association between these variants and low copy number was found and their possible negative role in mtDNA replication remains uncertain. Approximately 38% of the HTG patients with reduced copy number did not carry any exclusive D-loop or other mtDNA variants, which indicates that variants in nuclear-encoded mitochondrial genes, environmental factors, or aging might be involved in those cases. In conclusion, we found that variants in the D-loop region may be a risk factor in a subgroup of POAG, possibly by affecting mtDNA replication.